Paparan iklan junk food dan pola konsumsi junk food sebagai faktor risiko terjadinya obesitas pada anak sekolah dasar kota dan desa di Daerah Istimewa Yogyakarta - Esti Nurwanti; Hamam Hadi; Madarina Julia (Alma Ata University Press, 2013)
ABSTRACTBackground: Increasing prevalence of obesity may be caused by junk food advertised while children are watching television.Preference for foods requested by the children is much inﬂ uenced by junk food advertisement, so that it can affect calori intakeand correlates with obesity. Obesity in children can cause obesity during adulthood and may increase the risk of degenerativedisease, like diabetes and cardiovascular.Objective: To analyze the level of risk exposure to junk food advertising and junk food consumption on the incidence of obesityin primary school children in elementary school children at the area of Yogyakarta Municipality and District of Bantul.Method: This study was an observational study with case-control design. The study population was elementary school childrenin the City of Yogyakarta and Bantul Regency. Cases were elementary school children who were obese, while the controlswere children who were not obese and sat closest the cases regardless of age and sex. Number of subjects for each groupwere 244 (1:1). Obesity was deﬁ ned as BMI / U>95th percentile curves NCHS/CDC. Sampling to ﬁ nd obesity with probabilityproportional to size (PPS) and sampling for cases and controls using random sampling techniques. Univariate analysis ofthe data using frequency distributions, bivariate analysis using Chi-square, and multivariate analysis using multiple logisticregression. Data were analyzed using STATA 11 program with a 95% signiﬁ cance level and nutrisurvey.Result: Bivariate analysis using Chi Square shows the variables that inﬂ uence the incidence of obesity, such as junkfood ads exposure (OR=1.70, 95%CI: 1.17-2.48, and p=0.004), junk food energy intake (OR=1.58, 95%CI: 1.08-2.32and p=0.01), intake of saturated fat junk food (OR=1.74, 95%CI: 1.18-2.56 and p=0.004), sodium intake of junk food(OR=1.83, 95%CI: 1.25-2.69 and p=0.001) and sex (OR=0.58, 95%CI: 0.40-0.85 and p= 0.0035). Multivariate analysiswith logistic regression showed that the variables affect obesity is junk food ads exposure (OR=1.63, 95%CI: 1.13-2.36and p <0.05) and sex (OR=0.62, 95% CI:0.43-0.91 and p<0.05).Conclusion : Exposure to junk food advertising can increase the risk of obesity.KEYWORDS: obesity, ads, junk food, energy, saturated fat, natrium, sucroseABSTRAKLatar Belakang: Peningkatan prevalensi obesitas dapat disebabkan oleh iklan makanan junk food ketika anak menontontelevisi. Pemilihan makanan yang diinginkan oleh anak banyak dipengaruhi oleh iklan tersebut, sehingga mempengaruhiasupan kalori dan berkorelasi dengan obseitas. Obesitas pada anak dapat menyebabkan obesitas saat dewasa dandapat meningkatkan risiko penyakit degeneratif, seperti diabetes dan kardiovaskuler.Tujuan: Untuk mengukur tingkat risiko paparan iklan junk food dan konsumsi junk food terhadap kejadian obesitaspada anak SD di Kota Yogyakarta dan Kabupaten Bantul.Metode: Penelitian ini merupakan penelitian observasional dengan rancangan kasus-kontrol. Populasi penelitian adalah anak SD di Kota Yogyakarta dan Kabupaten Bantul. Kelompok kasus adalah anak yang mengalami obesitas,sedangkan kelompok kontrol adalah teman sekelas yang tidak mengalami obesitas dan duduk paling dekat di sebelahkanan kasus tanpa melihat umur dan jenis kelaminnya Jumlah subjek untuk masing-masing kelompok sebesar 244(1:1). Obesitas dideﬁ nisikan dengan IMT/U>persentil 95th kurva NCHS/CDC. Pengambilan sampel untuk menemukanobesitas dengan probability proportional to size (PPS) dan pengambilan sampel untuk kasus dan kontrol menggunakanteknik random sampling. Analisis univariat menggunakan distribusi frekuensi, analisis bivariat menggunakan Chi-square,dan multivariat menggunakan regresi logistik ganda. Data dianalisis dengan menggunakan program STATA 11 dengantingkat kemaknaan 95% dan nutrisurvey.Hasil: Analisis bivariat dengan Chi-square menunjukkan variabel yang berpengaruh dengan kejadian obesitas, di antaranyapaparan iklan junk food (OR=1,70, 95%CI:1,17-2,48, dan p=0,004), asupan energi junk food (OR= 1,58, 95%CI:1,08-2,32dan p=0,01), asupan lemak jenuh junk food (OR=1,74 95%CI 1,18-2,56 dan p=0,004), asupan natrium junk food (OR=1,83,95%CI:1,25-2,69 dan p=0,001) serta jenis kelamin (OR= 0,58, 95%CI:0,40-0,85 dan p= 0,0035). Hasil analisis multivariatdengan regresi logistik memperlihatkan variabel yang berpengaruh terhadap obesitas adalah paparan iklan junk food (OR=1,63,95%CI:1,13-2,36 dan nilai p <0,05) dan jenis kelamin (OR=0,62, 95%CI:0,43-0,91 dan p<0,05).Kesimpulan: Paparan iklan junk food dapat meningkatkan risiko terjadinya obesitas.KATA KUNCI: obesitas, iklan, junk food, energi, lemak jenuh, natrium, sukrosa